1974
DOI: 10.1002/kin.550060405
|View full text |Cite
|
Sign up to set email alerts
|

The reaction of trichloromethyl radicals with hydrogen chlorid and a new estimation of the rate of combination of trichloromethyl radicals

Abstract: The effect of the addition of hydrogen chloride on the photolysis of carbon tetrachloride in the presence of cyclohexane has been investigated in a companion paper. The data enable the rate constant ratio k8/(k5)1/2 to be determined. Since k−8 is well established, k5 can be estimated from known thermochemical data. The validity of the thermochemical derivation is checked by applying it to trifluoromethyl radicals. The photolysis of bromotrichloromethane and carbon tetrachloride in the presence of hydrogen chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1974
1974
1999
1999

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…This result indicates that the rate of the trichloromethyl radical self-reaction is clearly faster than the rate of • CCl 3 decomposition. Consistent with this argument is the fact that the rate constant for the self-reaction of the trichloromethyl radicals is to be 10 10 M -1 s -1 …”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…This result indicates that the rate of the trichloromethyl radical self-reaction is clearly faster than the rate of • CCl 3 decomposition. Consistent with this argument is the fact that the rate constant for the self-reaction of the trichloromethyl radicals is to be 10 10 M -1 s -1 …”
Section: Resultsmentioning
confidence: 83%
“…Consistent with this argument is the fact that the rate constant for the self-reaction of the trichloromethyl radicals is to be 10 10 M -1 s -1 . 36 In a recent study, Kruus et al 6 reported on their observations of the reaction intermediates produced during the sonication of aqueous chloroform solutions at 900 kHz at an acoustic power of 25 W and an applied power density of 0.17 W cm -3 . With an initial concentration of [CHCl 3 ] o ) 4.2 mM, Kruus et al observed the formation of carbon tetrachloride (18 µM), tetrachloroethene (43 µM), hexachloroethane (32 µM), pentachloroethane (17 µM), trichloroethene (10 µM), 1,1,2,2tetrachloroethane (3 µM), and hexachlorobutadiene (4 µM) after 10 min of sonication.…”
Section: Resultsmentioning
confidence: 99%
“…(c) CCl 3 + CCl 3 . The CCl 3 recombination reaction has been studied experimentally by several groups using indirect methods. The first direct measurement was reported by Danis et al who observed the time-resolved decay of CCl 3 by UV absorption. They determined the recombination rate coefficients over a wide temperature range.…”
Section: Resultsmentioning
confidence: 99%
“…It was mainly chosen because of the availability of extensive experimental and theoretical data. It also enables comparison of the results from this version of CFTST with the microcanonically and canonically derived rate coefficients for this recombination reaction by Wardlaw and Marcus . For the analogous halogenated systems (R2 and R3) there is, despite their importance, a substantial uncertainty in the experimentally determined rate coefficients, , especially for reaction R2. The main aim of the paper is to model the temperature dependence of the rate coefficients for three recombination reactions which are anticipated to become more sterically hindered as the reactants become bulkier.…”
Section: Introductionmentioning
confidence: 99%
“…(I) in Figure 1. Taking the rate constant for the combination of trichloromethyl radicals, k8 = L/mol-s, independent of temperature [12] we obtain a value of k6 = 108.4*0.4 exp[-(l0.0 f 0.7) kcal/mol/RT], which is in good agreement with that of Wampler and Kuntz [13], k6 = exp[-l0.7 kcal/mol/RT]. A few runs were carried out in which carbon tetrachloride was photolyzed in the presence of cyclopentane.…”
Section: Resultsmentioning
confidence: 99%